Tuning BMI.NTf2 Ionic Liquid Concentration in Dental Adhesives Towards a Rational Design of Antibacterial Materials - Isadora Martini Garcia; Andressa Simionato; Virgínia Serra Souza; Jackson Damiani Scholten; Mary Anne Sampaio Melo; Fabrício Mezzomo Collares (Applied Sciences)
1-Butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BMI.NTf2) is a hydrophobic ionic liquid with potential antibacterial properties for dental materials. This study aimed to (1) incorporate different mass fractions of BMI.NTf2 into a dental adhesive and (2) assess its impact on physical and chemical properties. Adhesive resins were prepared with 1 (G1%), 2.5 (G2.5%), and 5 wt.% (G5%) BMI.NTf2, with a control group (GCTRL) lacking the ionic liquid. Evaluations included polymerization kinetics, degree of conversion (DC), softening in solvent (ΔKHN%), and ultimate tensile strength (UTS). Groups with BMI.NTf2 showed accelerated polymerization kinetics, with G5% achieving a higher DC and ΔKHN% compared to GCTRL (p < 0.05). Lower concentrations (1% and 2.5%) did not affect ΔKHN%, and no significant differences were found in UTS across groups (p > 0.05). Notably, 2.5 wt.% of BMI.NTf2 increased the DC without affecting other properties, indicating optimal polymerization rates and handling characteristics. These results support the development of BMI.NTf2-based antibacterial adhesives that may assist in preventing secondary caries in restorative dentistry.